Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil - Elvira Elvira; Reska Nurvinanda; Atin Sagita (STIKES Citra Delima Bangka Belitung, 2023)
Anemia is a condition with hemoglobin, hematocrit and red blood cell levels lower than the normal value <11 gr/dl in pregnant women. Anemia in pregnancy has an unfavorable effect on the mother, both in pregnancy, childbirth and in the puerperium. The purpose of this study was to determine the relationship between age, pregnancy interval, parity, nutritional status, consumption of Fe tablets, ANC visits, and knowledge of the incidence of anemia in pregnant women in the working area of the Gerunggang Health Center, Pangkal Pinang City. This study used an analytic survey with a cross sectional approach. The number of respondents was 90 people at the Gerunggang Health Center, with the sampling technique using simple random sampling. The research instrument used a questionnaire. Using statistical analysis with the chi square test at the 95% confidence level (α = 0.05). The results of the study showed that pregnancy spacing (p value = 0.027), parity (p value = 0.02), nutritional status (p value = 0.001), adherence to consumption of Fe tablets (p value = 0.04) and knowledge (p value = 0.003) there is a significant relationship with anemia in pregnant women.